Artificial Super Neutrophils for Inflammation Targeting and HClO Generation against Tumors and Infections - Zhang, Chi; Zhang, Lu; Wu, Wei; Gao, Fan; Li, Run‐Qing; Song, Wen; Zhuang, Ze‐Nan; Liu, Chuan‐Jun; Zhang, Xian‐Zheng (Advanced materials (Weinheim), 2019)
Neutrophils are powerful effector leukocytes that play an important role in innate immune systems for opposing tumor progression and ameliorating pathogen infections. Inspired by their distinct functions against tumors and infections, the artificial “super neutrophils” are proposed with excellent inflammation targeting and hypochlorous acid (HClO) generation characteristics for targeting and eliminating malignant tumor cells and pathogens. The “super neutrophils” are fabricated by embedding glucose oxidase (GOx) and chloroperoxidase (CPO) into zeolitic imidazolate framework‐8 (ZIF‐8) for HClO generation via enzymatic cascades, and then encapsulating them with the neutrophil membrane (NM) for inflammation targeting. In vitro and in vivo results indicate that these artificial “super neutrophils” can generate seven times higher reactive HClO than the natural neutrophils for eradicating tumors and infections. The “super neutrophils” demonstrated here with easy fabrication and good neutrophil‐mimicking property exhibit great potential for biomedical applications. Artificial “super neutrophils” (GCZM) are designed to simulate the inflammation targeting and HClO generation functions of natural neutrophils. GCZM can accumulate in inflammation sites and exhibit high efficacy to generate highly toxic HClO for complete tumor and pathogen elimination.